Dietary Effects of Natural Polyphenol Antioxidant on Laying Performance and Egg Quality of Laying Hens Fed Diets with Oxidized Oil - Lee,HH (2019)
ABSTRACT This study was conducted to investigate the effects of dietary oxidized oil and natural polyphenol antioxidants on laying performances and egg quality of laying hens. A total of two hundred, 61-week-old Lohmann Brown laying hens were divided into five groups, consisting in four replicates of 10 birds each. They were fed one of the five experimental diets (fresh oil only, oxidized oil without antioxidants, oxidized oil with vitamin E 200 ppm, oxidized oil with vitamin E 100 ppm + Cabanin CSDⓇ 100 ppm, oxidized oil with Cabanin CSDⓇ 500 ppm)respectively, for 6 weeks. There were no significant differences in laying performances and egg weight among the treatments. However, egg mass in group fed oxidized oil with vitamin E 100 ppm + Cabanin CSDⓇ 100 ppmwas significantly higher than group fed oxidized oil only (p<0.05). Eggshell thickness and eggshell strength was not affected by feeding of oxidized oil and antioxidants. Haugh unit checked after storage of 14 d from the end date of the trial showed significant difference (p<0.05). Serum superoxide dismutase (SOD) like activity was significantly higher in antioxidant treated groups. The level of serum glutamic oxaloacetic transaminase (GOT) was significantly lower in groups fed vitamin E 100 ppm + Cabanin CSDⓇ 100 ppm or Cabanin CSDⓇ 500 ppm compared to groups fed oxidized oil without antioxidant. The number of total microbes, lactobacilli, and Enterocossus faecium showed significant difference favored to antioxidants groups. This study indicates that addition of oxidized oil to layer diet may have harmful effect on oxidative status and egg quality, but concurrent addition of vitamin E and natural polyphenol can alleviate the toxic effect of oxidized oil.